Implementation of the Full-Day School System to Promote the Quran Memorization Program at Al-Madinah Balong Integrated Elementary School in Ponorogo - arief rohmatulloh; Umar Sidiq (Prodi PAI, Fakultas Tarbiyah, UNIDA GONTORs Tarbiyah, Universitas Darussalam Gontor, 2026)
Qur’an memorization programs in Islamic elementary schools face serious challenges, including limited time within the regular curriculum, insufficient oversight of memorization quality, and excessive academic workload. To respond to these ongoing challenges, MI Terpadu Al-Madinah Balong has adopted a full-day school (FDS) model that merges general academic subjects with Islamic education under an extended daily learning structure. The present study aims to: (1) explore how the full-day school model is put into practice in reinforcing the Quran memorization program; (2) outline the processes through which its implementation takes place; and (3) determine the impact of this model on the memorization achievements of students. This research employed a descriptive qualitative methodology with a case study framework. Primary data were collected through direct observation, in-depth interviews, and documentary analysis, subsequently processed using the interactive analytical model developed by Miles, Huberman, and Saldana. The expected outcomes of this study include identifying successful implementation strategies, approaches to incorporating tahfīẓ activities into the FDS structure, and the role of this integration in advancing students' memorization proficiency and nurturing their religious character. This study is also expected to offer practical insights to advance Islamic education management, particularly in developing integrated and sustainable tahfīẓ programs at the madrasah ibtidaiyah level.